Determination of tafenoquine in dried blood spots and plasma using LC and fluorescence detection. (August 2011) - Römsing, Susanne; Lindegardh, Niklas; Bergqvist, Yngve
Background: The growing problem of parasites developing resistance to the traditional antimalarial drugs makes the development of new effective and safe drugs crucial. Tafenoquine is a new promising antimalarial drug for prophylaxis and treatment.Results: A bioanalytical method for the determination of tafenoquine in 100 µl of capillary blood applied onto sampling paper and in 100 µl of plasma has been developed and validated. The Whatman 31 ET Chr paper was treated with 0.6 mol/l tartaric acid to improve the extraction recovery and solid-phase extraction was used for cleanup procedure of the blood samples. Plasma samples were precipitated with methanol. Tafenoquine and internal standard were separated on a Zorbax SB-CN column by reversed-phase LC and detected with fluorescence detection at 262 and 470 nm. The within- and between-day variations were below 10 and 14%, respectively, over the range 50–200 nmol/l for capillary blood on sampling paper and below 6 and 10% for plasma samples. The LLOQ of the method was 50 nmol/l.Conclusion: The developed method has adequate sensitivity and is highly suitable for clinical studies in dried blood spots and plasma.